2009
DOI: 10.1073/pnas.0810200106
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the North American “Dust Bowl” drought through human-induced land degradation

Abstract: The ''Dust Bowl'' drought of the 1930s was highly unusual for North America, deviating from the typical pattern forced by ''La Nina'' with the maximum drying in the central and northern Plains, warm temperature anomalies across almost the entire continent, and widespread dust storms. General circulation models (GCMs), forced by sea surface temperatures (SSTs) from the 1930s, produce a drought, but one that is centered in southwestern North America and without the warming centered in the middle of the continent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
277
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 312 publications
(293 citation statements)
references
References 27 publications
13
277
0
3
Order By: Relevance
“…Conversion of desert and grassland to cropland, grazing, fire suppression, introduction of invasive species, disturbances leading to soil erosion and blowing dust, and the development of urban areas have all likely had impacts on regional climate. No systematic studies on these land cover changes and their impacts on climate or drought have been undertaken (68), but these changes are another important reason that droughts of the past are unlikely to be an exact analogue for current and future droughts. In addition, from an impacts standpoint, droughts have a much broader range of impacts on human activities today than in the past because of today's greater demands on limited water resources.…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of desert and grassland to cropland, grazing, fire suppression, introduction of invasive species, disturbances leading to soil erosion and blowing dust, and the development of urban areas have all likely had impacts on regional climate. No systematic studies on these land cover changes and their impacts on climate or drought have been undertaken (68), but these changes are another important reason that droughts of the past are unlikely to be an exact analogue for current and future droughts. In addition, from an impacts standpoint, droughts have a much broader range of impacts on human activities today than in the past because of today's greater demands on limited water resources.…”
Section: Discussionmentioning
confidence: 99%
“…While several papers have speculated that these landscape changes may have amplified these droughts (Feng et al 2008;Seager et al 2008b), only one study to date has explicitly tested surface impacts on the megadroughts within a modeling framework (Cook et al 2011). They found that vegetation mortality alone (i.e., without wind erosion or dust feedbacks) was insufficient to amplify the modelsimulated droughts or reproduce the drought persistence seen in the paleorecord.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the JJA focus of the NADA, PDSI has a memory time scale of about 12-18 months (Guttman 1998;Vicente-Serrano et al 2010), allowing it to incorporate information on temperature and precipitation throughout the year. PDSI from the NADA has been used with good success to validate and inform a variety of modeling studies investigating historical and paleo-droughts over North America (e.g., Cook et al 2011;Herweijer et al 2006Herweijer et al , 2007Oglesby et al 2012;Seager et al 2008a). …”
Section: A North American Drought Atlasmentioning
confidence: 99%
See 2 more Smart Citations